2018
DOI: 10.1016/j.chempr.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Activating p-Blocking Centers in Perovskite for Efficient Water Splitting

Abstract: Redox activity has been considered the descriptor of the catalytic performance of transition-metal oxides with the crystal family of ABO 3 perovskites. Although elemental doping is an efficient way to promote their activity for water splitting, most research has been centered only on the influence of doping A/B sites. This work demonstrates that F-anion substitution can make the O p band closer to the Femi level and activate the lattice O forming mobile O*. These features help regulate the lattice O sites in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 45 publications
2
77
0
1
Order By: Relevance
“…The insert in the Fig. 1 (d) is the O K-edge and Co L -edge fine structure, which is similar with the EELS results of the PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 5 + δ and La 0.5 Ba 0.25 Sr 0.25 CoO 3 −δ [34][35][36] . These results indicate that the double perovskite oxide NBCCF has been successfully synthesized.…”
Section: Resultssupporting
confidence: 81%
“…The insert in the Fig. 1 (d) is the O K-edge and Co L -edge fine structure, which is similar with the EELS results of the PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 5 + δ and La 0.5 Ba 0.25 Sr 0.25 CoO 3 −δ [34][35][36] . These results indicate that the double perovskite oxide NBCCF has been successfully synthesized.…”
Section: Resultssupporting
confidence: 81%
“…In addition to cation doping, Hua et al reported that anion-F doping into perovskites can shift up the p-band center and activate the redox activity of the lattice oxygen for the OER on La 0.5 Ba 0.25 Sr 0.25 CoO 2.9-d F 0.1 . 130,131 Moreover, F-anion centers play a key role in electron traps, controlling the charge compensation process between the catalysts and reaction intermediates, which allows fast proton-electron transfer. Thus, La 0.5 Ba 0.25 Sr 0.25 CoO 2.9-d F 0.1 exhibits higher activity than RuO 2 and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-d .…”
Section: Introducing a Proton Acceptor Group (*Oo + *H)mentioning
confidence: 99%
“…ABO 3 perovskites have been widely applied as functional electrode materials in catalytic system with promising performance . In addition, remarkable advancements in the catalytic mechanism regarding the water splitting system for perovskite have been achieved . Latest research uncovered the nature of transition‐metal ion in B‐site of perovskite partly governs the intrinsic catalytic activity, thus the selection of B‐site ion is of paramount importance .…”
mentioning
confidence: 99%